Formation and growth mechanism of the α2 lath within the γ phase in high Nb containing TiAl alloy - Gengwu Ge; Gang Yang; Yingchao Guo; Yongfeng Liang; Junpin Lin (Journal of Materials Research and Technology)
A high Nb containing TiAl alloy exhibiting near fully lamellar microstructure with nano-lamellar spacing was obtained via heat treatment. The lamellar structure exhibits an average spacing of approximately 75 nm and comprises both γ/α₂ and γ/γ interfaces. Subsequent multiaxial compression led to the development of a basketweave microstructure composed of crisscross α₂ laths within γ grains. The α2 phase exhibit different orientations, resulting from the precipitation along the equivalent planes {111}γ within the equiaxed γ grains. The growth of the α2 phase proceeds through the “terrace-ledge-kinking” mechanism. The long periodic stacking ordered structure, 6H, is an intermediate structure during the γ→α phase transformation. The γ phase, α2 phase and 6H satisfy the orientation relationship: (111)γ//(0001)α2//(0006)6H, [1‾ 10]γ//[11 2‾ 0]α2//[01 1‾ 0]6H. The microhardness of the alloy with basketweave microstructure is higher than the as-cast alloy.